Study Protocol of the ESAP Study: Endoscopic Papillectomy vs. Surgical Ampullectomy vs. Pancreaticoduodenectomy for Ampullary Neoplasm—A Pancreas2000/EPC Study - Hollenbach, Marcus; Ali, Einas Abou; Auriemma, Francesco; Gulla, Aiste; Heise, Christian; Regnér, Sara; Gaujoux, Sébastien (Frontiers in Medicine, 2020)
Background: Lesions of the Ampulla of Vater are a rare condition, representing less than 10% of periampullary neoplasms. Nevertheless, ampullary adenomas have the potential for malignant transformation to ampullary carcinomas by an adenoma-to-carcinoma sequence. Thus, adequate patient selection and complete R0 resection of non-invasive ampullary lesions either by endoscopic ampullectomy (EA), surgical ampullectomy (SA) or pancreaticoduodenectomy (PD) is essential. Although PD was traditionally performed, recent studies reported considerable efficacy and fewer complications following EA and SA. Since consistent comparative data are lacking, the Endoscopic versus Surgical Ampullectomy versus Pancreaticoduodectomy (ESAP) study will provide evidence for a therapeutic standard and post procedure morbidity in ampullary lesions. Methods: International multicenter retrospective study. Adult patients (>18 years of age) who underwent SA or PD for ampullary neoplasm between 2004 and 2018 or EA between 2007 and 2018 will be evaluated. Main inclusion criteria are ampullary lesions strictly located to the ampulla. This includes adenoma, adenocarcinoma (T1 and T2), neuroendocrine tumors, gastrointestinal stroma tumors and other rare conditions. Exclusion criteria are periampullary lesions, e.g. from the duodenal wall or the head of the pancreas, and interventions for tumor stages higher than T2. The main objective of this study is to analyze rates of complete resection (R0), recurrence and necessity for complementary interventions following EA, SA and PD. Treatment-quality for each procedure will be defined by morbidity, mortality and complication rates and will be compared between EA, SA and PD. Secondary objectives include outcome for patients with incomplete resection or initially understated tumors, lesions of the minor papilla, hereditary syndromes, neuroendocrine tumors, mesenchymal lesions and other rare conditions. Additionally, we will analyze therapy by argon plasma coagulation and radiofrequency ablation. Furthermore, outcome in curative and palliative interventions can be distinguished. Conclusion: The ESAP study will provide evidence for therapeutic algorithms and data for the implementation of guidelines in the treatment of different types of ampullary tumors, including recurrent or incomplete resected lesions.